2011
DOI: 10.1002/bjs.7295
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of treatment and outcome information between a clinical trial and the National Cancer Data Repository

Abstract: The National Cancer Data Repository demonstrates potential for informing clinical trials, but limitations prevent full intention-to-treat analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…The increased trend for laparoscopic surgery has been demonstrated in other studies9, 10, but they examined only operations recorded as being completed laparoscopically and the coding of such procedures is often inaccurate in routine data sets4. In the present study the total number of operations attempted laparoscopically was calculated by including all procedures coded as laparoscopically converted.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The increased trend for laparoscopic surgery has been demonstrated in other studies9, 10, but they examined only operations recorded as being completed laparoscopically and the coding of such procedures is often inaccurate in routine data sets4. In the present study the total number of operations attempted laparoscopically was calculated by including all procedures coded as laparoscopically converted.…”
Section: Discussionmentioning
confidence: 93%
“…Laparoscopic surgery can be challenging technically and associated with a long learning curve1–3. Although randomized trials provide evidence, their results may not always be directly transferable to the general population1, 4. Monitoring the introduction and outcomes of laparoscopic colorectal cancer surgery ensures that patients receive quality care in a cost‐effective manner.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study, however, identified colorectal cancer patients enrolled in a randomised trial within the NCDR and found excellent agreement in the information recorded in both datasets with regard to both treatment and outcomes 30. This demonstrated that the data within the NCDR were sufficient to monitor 30-day postoperative mortality across the country.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, comparisons of the information held in HES to that collected by clinical trials suggests that agreement is good for cases of confirmed cancer. 35 As a result, such linked data will provide the most robust figures possible.…”
Section: Discussionmentioning
confidence: 99%